Biopirataria e contrabando da biodiversidade amazônica: a cartografia dos crimes ambientais no Estado do Pará - AVIZ, Anderson da Silva (2022)
The present research seeks to address the crimes of biopiracy and smuggling that occur in the territory of the State of Pará. Located in the northern region, the state is one of many that make up the Brazilian Amazon. Holder of a rich biodiversity and traditional knowledge within its political and territorial boundaries, the state has been and continues to be the target of biopiracy and smuggling crimes since its colonization by the Portuguese. Crimes such as biopiracy and smuggling of plant or animal species have a high value in parallel trade, thus having impacts not only on the economy, but also on the cultural aspects of the people who have their subsistence, religion, and culture linked to extractivism and forest biodiversity. The general objective of this study is the spatialization of the crimes that occur in the state, within a time frame of ten years. The research was developed from documentary research and digital cartography, in order to spatially visualize the municipalities where the crimes took place. In an analysis from 2012 to 2021, the 144 municipalities of the state of Pará were analyzed and had their reports represented in the form of maps.